Prevalence and predictors of developing vision-threatening diabetic retinopathy within the first three years of type 2 diabetes - Yan, Jia; Li, Bo; Chen, Ye; Gu, Chufeng; Dai, Guosheng; Zhang, Qin; Zheng, Zhi; Luo, Dawei; Zhao, Shuzhi; Zhou, Chuandi (Frontiers in Endocrinology, 2023)
Purpose To investigate the prevalence of diabetic retinopathy (DR) and vision-threatening DR (VTDR) in patients with type 2 diabetes mellitus (T2DM) stratified by the duration of diabetes and to identify the clinical variations and risk factors for VTDR occurring at different stages of T2DM. Methods This was a retrospective comparative study. Patients were divided into short- (≤3 years), intermediate- (3–7 years), and long-duration (>7 years) groups. All patients were followed-up for DR and VTDR development. Risk factors were explored using logistic regression analysis. Results A total of,2961 patients were included; among them, 1,036 (35.0%) patients developed DR, and 293 (9.9%) had VTDR. The frequency of VTDR in patients who developed DR in the short-duration group was significantly higher than that in the intermediate-duration group (25.7% vs. 15.0%; p = 0.019), but comparable with that of the long-duration group (25.7% vs. 31.8%; p = 0.138). Patients who developed VTDR within the first 3 years of T2DM were more likely to have a family history of diabetes (p = 0.024), had higher glycated hemoglobin (p = 0.025), were males (p = 0.042), and were notably older at the onset of diabetes (p <0.001) but younger when diagnosed with DR (p <0.001). Moreover, higher glycated hemoglobin (OR = 1.14; 95% CI: 1.00–1.29; p = 0.043) and diabetic nephropathy (DN) (OR = 2.31; 95% CI: 1.08–4.91; p = 0.030) were independent risk factors for developing VTDR during the first 3 years of T2DM. Conclusion The risk of DR is not high in persons with ≤3 years’ duration of T2DM, however, if afflicted, the risk of VTDR should never be neglected. More frequent retinal screening is warranted in patients with newly diagnosed T2DM.